Combination of hyper-CVAD with ponatinib as first-line therapy for patients with Philadelphia chromosome-positive acute lymphoblastic leukaemia: long-term follow-up of a single-centre, phase 2 study. Issue 12 (December 2018) - Jabbour, Elias; Short, Nicholas J; Ravandi, Farhad; Huang, Xuelin; Daver, Naval; DiNardo, Courtney D; Konopleva, Marina; Pemmaraju, Naveen; Wierda, William; Garcia-Manero, Guillermo; Sasaki, Koji; Cortes, Jorge; et al.
Summary: Background: The combination of chemotherapy and ponatinib in Philadelphia chromosome-positive acute lymphoblastic leukaemia has the potential to be a new standard of care for the disease; however, long-term efficacy and safety data are needed. Our aim was to evaluate the long-term efficacy and safety of this regimen in patients with newly diagnosed Philadelphia chromosome-positive acute lymphoblastic leukaemia in this ongoing phase 2 trial. Methods: In our single-centre, phase 2, single-arm trial in the USA, adult patients with previously untreated Philadelphia chromosome-positive acute lymphoblastic leukaemia were sequentially enrolled. Eligible patients had newly diagnosed Philadelphia chromosome-positive acute lymphoblastic leukaemia, were aged 18 years or older, had an Eastern Cooperative Oncology Group performance status of 2 or less, a left ventricular ejection fraction above 50%, and adequate hepatic and renal function (serum bilirubin ≤3·0 mg/dL and serum creatinine ≤3·0 mg/dL, unless higher levels were believed to be due to leukaemia at the discretion of the investigator). Patients received eight cycles of 21 days, alternating between two drug combinations: hyper-fractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone (hyper-CVAD) and high-dose methotrexate and cytarabine. Ponatinib was given orally at 45 mg per day for the first 14 days of cycle 1 then continuously at 45 mg per day for the subsequent cycles. After 37 patients were treated, the protocol was amended to reduce the dose of ponatinib to 30 mg per day at cycle 2, with further reduction to 15 mg once a complete molecular response (defined as absence of quantifiable BCR-ABL1 transcripts) was achieved. Patients in complete remission received maintenance with ponatinib daily (30 mg or 15 mg) indefinitely, and with vincristine (2 mg intravenously on day 1) and prednisone (200 mg orally on days 1–5) monthly for 2 years. The primary endpoint was 3-year event-free survival in the intention-to-treat population. The trial is registered atClinicalTrials.gov, numberNCT01424982, and is ongoing and still enrolling patients. Findings: 76 patients with a median age of 47 years (IQR 39–61) were enrolled and treated between Nov 19, 2011, and April 4, 2018. The 3-year event-free survival was 70% (95% CI 56–80). The most common grade 3 or 4 adverse events were infection (n=65, 86%), increased transaminases (n=24, 32%), increased bilirubin (n=13, 17%), pancreatitis (n=13, 17%), hypertension (n=12, 16%), bleeding (n=10, 13%), and skin rash (n=9, 12%). Six patients died while still on study treatment. Three patients (4%) died from infection and one (1%) from haemorrhage. Two patients died from myocardial infarction related to early ponatinib use; neither death occurred after protocol revision. Interpretation: The combination of chemotherapy with ponatinib is effective in achieving long-term remission in patients with newly diagnosed Philadelphia chromosome-positive  acute lymphoblastic leukaemia. This regimen could represent a new standard of care for this population. A randomised, phase 3 study to evaluate the efficacy of this combination compared with chemotherapy plus earlier-generation tyrosine-kinase inhibitors is warranted. Funding: Takeda Oncology.